Dermoscopic Findings in 126 Patients with Alopecia Areata: A Cross-Sectional Study - Mahmoudi, Hamidreza (Int J Trichology, 2018)
BACKGROUND: Dermoscopy is used increasingly in dermatological practice. Although dermoscopic findings of alopecia areata (AA) are described in the literature, studies are limited. AIM: Our aim was to evaluate dermoscopic findings of Iranian patients with AA and correlate them with disease activity and severity. SUBJECTS AND METHODS: Totally 126 patients were examined using a Dermlite II multispectral dermoscope. Severity, activity, pull test, nail changes, treatments, and dermoscopic findings were recorded. STATISTICAL ANALYSIS USED: Statistical analysis was done by SPSS version 22, using appropriate statistical tools. RESULTS: The most common dermoscopic findings were yellow dots (84.1%), vellus hairs (62.6%), black dots (48.4%), exclamation mark (30.9%), and broken hair (9.5%), in decreasing order. Furthermore, the most common dermoscopic findings in patients on diphencyprone were vellus hairs and yellow dots. Yellow dots and vellus hairs were most common in patients with alopecia universalis. However, broken hairs and exclamation mark hairs were mostly observed in patchy multiple AA patients. Yellow dots and exclamation mark hairs were also significantly more common in patients with positive pull test. Furthermore, vellus hairs were more common in patients with remitting disease pattern. With regard to scalp severity, yellow dots related positively, while vellus hairs, broken hairs, and exclamation mark hairs related negatively with severity of disease. CONCLUSIONS: Dermoscopic findings differ in various stages of activity and severity of AA. Dermoscopy is a valuable tool for the dermatologist for the diagnosis, follow-up, and evaluation of response to treatment.